Communication development and theatre use in Africa - Warritay, Batilloi (1988)
"This article observes that the rich potentials of theatre as a media of development communication Africa has not been adequately tapped and so makes a strong submission for greater use of theatre for development purposes in the continent. It examines three dominant methods of theatre use for development and other types of communication and points out that theatre can be used interactively or independently as a medium of communication. The three key methods analyzed by the article are the Agitrop method, participatory theatre and the Forum method. The article reported six cases of theatre use for various projects in six African countries and concludes that the role of today's African communicator must be such that relevant communication forms are used in an interactive manner for the largest segments of African nations and people." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-16258